Kinerja Pelayanan Administrasi Akademik SMP Josua Kota Bambu Menggunakan Metode Importance Performance Analysis - Yesica Amelia Octaviana Sitorus; Nur Nawaningtyas Pusparini; Asrul Sani (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
Technological advancements in Indonesia have resulted in many improvements that have enhanced product quality and overall success for various sectors, including industry, education for a school, academic satisfaction is more aimed at students because they are the main customers of the school or educational institution. Due to the level of effectiveness and consumer service, it is very important to know the level of satisfaction that consumers have received and the sustainability of these educational institutions, where students are the main consumers at Josua Junior High School .IPA helps identify attributes that need to be improved and how to implement them. By improving service quality, it can be more in line with consumer satisfaction and satisfaction with the education system. Based on the results of the analysis using this method, it can be seen that the distance or gap between perceptions and expectations from all aspects of the assessment is negative with the tangible dimension of -0.73, then the reliability dimension gets -0.71, the responsiveness dimension gets a value of -0.73. In conclusion, technological developments in Indonesia have led to many improvements that can enhance product quality, consumer satisfaction, and overall success.